2000
DOI: 10.1046/j.1365-3113.2000.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Neotropical Lepidocyrtus (Collembola: Entomobryidae): first assessment of patterns of speciation in Puerto Rico and phylogenetic relevance of some subgeneric diagnostic characters

Abstract: Summary A phylogenetic analysis of the Neotropical members of genus Lepidocyrtus was conducted to assess the pattern of speciation in Puerto Rico while testing the phylogenetic information content of two characters used to diagnose subgenera. The analysis included twenty‐two species of Lepidocyrtus from the Neotropical Region for which information on the tergal chaetotaxy of the trunk was available, two species of Holarctic Lepidocyrtus, three species of Pseudosinella, two species of Metasinella used in outgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The largest two genera Lepidocyrtus and Pseudosinella are simply separated by number of ommatidia, and Pseudosinella includes lineages considered as derived independently from various Lepidocyrtus species (Christiansen ; da Gama ). Phylogenetic works by Christiansen & Bellinger () and Soto‐Adames (, ) further indicated the complexity of Lepidocyrtinae.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The largest two genera Lepidocyrtus and Pseudosinella are simply separated by number of ommatidia, and Pseudosinella includes lineages considered as derived independently from various Lepidocyrtus species (Christiansen ; da Gama ). Phylogenetic works by Christiansen & Bellinger () and Soto‐Adames (, ) further indicated the complexity of Lepidocyrtinae.…”
Section: Discussionmentioning
confidence: 94%
“…The largest two genera Lepidocyrtus and Pseudosinella are simply separated by number of ommatidia, and Pseudosinella includes lineages considered as derived independently from various Lepidocyrtus species (Christiansen 1961;da Gama 1984). Phylogenetic works by Christiansen & Bellinger (1991) and Soto-Adames (2000 further indicated the complexity of Lepidocyrtinae. Most characters are morphologically fairly conserved and result in well-known difficulties for identifying lepidocyrtins, considered to be among the most problematic collembolan taxa (Deharveng 2004).…”
Section: Subfamily Heteromurinae Heteromurini Absolon and Kseneman 1942mentioning
confidence: 97%
“…). However, this subdivision is not universally accepted, and a general re‐evaluation of many of the characters used has been advocated (Soto‐Adames ). Characters used to recognize genera, subgenera and species within Lepidocyrtinae range from size and shape of the body, or parts of the body, to the many characters within body chaetotaxy (Yosii ; Gisin , ; Szeptycki , ; Mateos , ).…”
Section: Methodsmentioning
confidence: 99%
“…species and questioned the reliability of dental tubercle. Later, Soto-Adames (2000) made a phylogenetic analysis of Neotropical members of the genus, disagreeing with the previous conclusion and considering that this character has phylogenetic information useful in defining Yoshii’s subgenera; he also suggested that dental tubercle should be used in combination with other characters. Considering the availability of this character in most literature descriptions and how easily it can be observed in practice, we considered that its use at generic level is relevant.…”
Section: Introductionmentioning
confidence: 90%